Effect of long-term grazing with goats on the natural state and economic value of vegetation in North Hungarian Mountains grasslands - Turcsányi-Járdi, Ildikó; Balogh, Petra; Bajnok, Márta (JOURNAL OF LANDSCAPE ECOLOGY, 2024)
In the present study, we processed the cenological data of 4 sample areas of two settlements in the North Hungarian Mountains. The plots are almost identical in size (2.4-2.5 ha) and have been grazed and mowed by goats for 20-25 years. The sample plots are: N1: Nagyréde overgrazed goat pasture. N2: Nagyréde meadow. C1: Csokvaomány low grazing pressure goat grazing grassland. C2: Csokvaomány mowed and grazed. In each area 6-6 cenological records were taken randomly. The objective was to compare the vegetation of different grazing pressure and grassland management areas with goats over a long period of 20-25 years of continuous grazing. How valuable is it for conservation and grassland management? Based on the study of the grasslands established under long-term management, mowing and grazing could be a sustainable management form for the utilisation of these semi-arid grasslands in the Pannonian region. Grazing with goats also provides opportunity of maintaining the condition of the grassland. Overgrazed grassland, when grazed with 24 mother goats and their offspring over an area of 2.5 ha, resulted in the most degraded vegetation community. This was reflected in the species composition since most of the species were weeds and disturbance tolerants. Nevertheless, the number of species A was higher than in the meadow(N2), but this was due to the high number of weeds. The overgrazed N1 grassland also had a low value in the Balázs grassland assessment number. The low grazing pressure grassland (C1) also had a significant number of species indicative of degradation, but the proportion of weeds was low. In terms of grassland management and biomass values the mown grassland was the most valuable grassland of all those studied. Based on the species composition of the areas the values of the meadow (N2) and subsequently grazed goat pasture (C2) in were particular outstanding. The meadow (N2) contains nearly double the value of the number of species, which results in the stability of the lawn, so it is believed that it will be more resistant to the changing climate in the future. Based on the present study, the combination of light grazing pressure and mowing is best suited for the management and economic utilization of these semi-arid grasslands.